Situation of Rabies in Ethiopia: A Five-Year Retrospective Study of Human Rabies in Addis Ababa and the Surrounding Regions. (19th February 2021) - Aklilu, Mesfin; Tadele, Wogayehu; Alemu, Amelework; Abdela, Sintayehu; Getahun, Garuma; Hailemariam, Alemnesh; Tadesse, Yirgalem; Kitila, Gutu; Birhanu, Endalkachew; Fli, Ibsa; Getachew, Abebe; Mulugeta, Yimer
Abstract : Objective . The study objective was to estimate the burden of human rabies in Ethiopia from 2015–2019. Study Design . A descriptive study design was applied to measure the size of the problem. Method . Retrospective data were used from the Ethiopian Public Health Institute rabies case record book that was registered between 2015 to 2019. Result . Eighty-seven (87) cases of human rabies were diagnosed clinically in the Ethiopian Public Health Institute over the period of five years (2015–2019) with 100% case fatality. Of these, 83 (95.4%) cases were attributed to dog bites, whereas 1 (1.1%) to a cat and 3 (3.4%) to wild animals. The fatalities were from Oromia ( n = 51 (58.6%), 13 (14.9%) were from Amhara, 15 (17.2%) were from Addis Ababa, and 8 (9.2%) from the Southern region. All referred cases had no record of immunization against rabies except eight. Ineffective postexposure treatment was the reason for 5 (5.7%) deaths. Out of 1, 652 brain samples of different animals, mainly dogs, submitted for examination, 1, 122 (68%) were found to be positive for rabies by the FAT. Dog bites were more common among males than females. The number of dog bite victims who had visited the EPHI counseling office and recommended to take postexposure prophylaxis against rabies both from Addis Ababa and the surrounding areas were 9, 592 and 4, 192, respectively. Out of these, 5, 708 were males and 3, 884 females for the capital Addis Ababa. Similarly, 2, 439 males and 1, 753 females account for areas surrounding Addis Ababa. Among those exposed from Addis Ababa, 1, 079 (11.2%) were in the age group less than five, 1696 (17.7%) were in the age group 6–13, and 6, 817 (71.1%) in the age group 14 and greater. Victims from outside of the capital Addis Ababa account for 644 (15.4%) for the age group less than 5 years, 964 (23%) for the age group 6–13 and, 2, 584 (61.6%) for the age group 14 and greater. Conclusion . Mechanisms must be sought to reduce the cost of PEP and means of obtaining funds so as to initiate timely treatment for rabies exposed individuals of low socioeconomic status. Besides prevention, strategies should focus on public education and strict dog population control.